Meat quality of (Bos indicus) cattle finished on different concentrate feeds - Gebremariam, Tsegay Teklebrhan (Acta Scientiarum. Animal Sciences, 2022)
The study investigated meat quality of bulls fed concentrate feeds and hay. The treatments were hay ad libitum + dried cafeteria leftover 4 kg DM d-1 (D1); hay ad libitum + wheat bran 4 kg DM d-1 (D2); hay ad libitum + 4 maize grain 4 kg DM d-1 (D3); hay ad libitum + mix 4 kg DM d-1 (1:1, wheat bran to maize grain, respectively (D4)); hay ad libitum + scrambled whole groundnut 4 kg DM d-1 (D5); and hay ad libitum + mix of each ingredient 4 kg DM d-1(D6)). Samples from longissimus lumborum muscle were taken in triplicate. Beef from bulls fed D5 had highest (p < 0.05) protein and fat than those fed other treatments. However, bulls finished in D3 had similar fat to those fed with whole ground nut. Highest meat tenderness (p < 0.05) recorded at 24th followed by 16th d than those aged on other periods. Beef from D6 produced lean meat, which is acceptable to consumer and market demand than D3, produced carcass with highest fat coverage This study confirmed that meat from D6 had an acceptable quality attribute suggesting the breed could serve as a potential source in red meat industry.